2016
DOI: 10.52904/0718-4646.2016.455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de supervivencia y desarrollo inicial de 42 progenies de Peumo (Cryptocarya alba (Mol.) Looser) establecidas en la provincia de Arauco, Región del BioBío, Chile

Abstract: Se analiza la supervivencia y crecimiento inicial de un ensayo de 42 progenies y 18 procedencias de peumo (Cryptocarya alba) de 15 meses de edad, establecido en la comuna de Cañete (Provincia de Arauco, región del Biobío). Se evalúa también el efecto de dos tipos de protectores individuales de plantas sobre la supervivencia y crecimiento del ensayo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In Chile, some studies support the use of eco-technologies (e.g., tree shelters, fertilizers, mulching, and hydrogel) and proper establishment design in planting seedlings to alleviate those stresses and increase plant survival and growth [18,23]. Tree shelters were initially designed to protect plants from animal browsing, but several studies have shown their positive effect on survival in the Mediterranean and semiarid zones by reducing the light and thermal stress at outplanting (i.e., shading effect of shelters) [24][25][26][27]. However, the effect of shading through shelters and light transmissivity is species-specific and determined by site factors such as temperature and water stress experienced by plants [28].…”
Section: Introductionmentioning
confidence: 99%
“…In Chile, some studies support the use of eco-technologies (e.g., tree shelters, fertilizers, mulching, and hydrogel) and proper establishment design in planting seedlings to alleviate those stresses and increase plant survival and growth [18,23]. Tree shelters were initially designed to protect plants from animal browsing, but several studies have shown their positive effect on survival in the Mediterranean and semiarid zones by reducing the light and thermal stress at outplanting (i.e., shading effect of shelters) [24][25][26][27]. However, the effect of shading through shelters and light transmissivity is species-specific and determined by site factors such as temperature and water stress experienced by plants [28].…”
Section: Introductionmentioning
confidence: 99%